Indonesia Gelap: Telaah Filsafat Etika terhadap Moral dan Kepemimpinan : Dark Indonesia: A Philosophical Study of Ethics on Morals and Leadership - Rohilah Rohilah; Mohamad Hudaeri; Agus Ali Dzawafi (Jurnal Filsafat Indonesia, 2026)
After the 2024 Election, the emergence of the hashtag #IndonesiaGelap on social media has become a symbol of public unrest regarding the direction of national leadership. This wave of criticism reflects a moral crisis and loss of public trust in the practice of power that is considered to deviate from basic values ​​such as justice, integrity, and trust. This phenomenon indicates a degradation of ethics in politics and government. This article aims to examine this phenomenon through an ethical philosophy approach, using the framework of Aristotle and Immanuel Kant's thinking. The research method used is qualitative-critical with interpretive-reflective analysis techniques on library data and media discourse. The results of the study show that in the context of Aristotle, Indonesian leadership lacks aretê (moral virtue) and deviates from telos (moral purpose) in the form of common welfare. Meanwhile, from Kant's perspective, the leader's actions fail to fulfill the categorical imperative principle, because they are based more on the desire for power than on universal moral principles. The conclusion of this study emphasizes the need to renew ethical values ​​in the practice of national leadership. Restoring the legitimacy of power is not enough only through structural reform, but also through the revitalization of public ethics and moral partisanship towards the people. This research is expected to contribute to building a more ethical, democratic, and public interest-oriented leadership model